Postprandial Hypertriglyceridaemia Revisited in the Era of Non-Fasting Lipid Profile Testing: A 2019 Expert Panel Statement, Narrative Review - Kolovou, Genovefa D.; Watts, Gerald F.; Mikhailidis, Dimitri P.; Pérez-Martínez, Pablo; Mora, Samia; Bilianou, Helen; Panotopoulos, George; Katsiki, Niki; Ooi, Teik C.; Lopez-Miranda, José; Tybjærg-Hansen, Anne; Tentolouris, Nicholas; et al. (Current Vascular Pharmacology, 2019)
Postprandial hypertriglyceridaemia, defined as an increase in plasma triglyceride-containing lipoproteins following a fat meal, is a potential risk predictor of atherosclerotic cardiovascular disease and other chronic diseases. Several non-modifiable factors (genetics, age, sex and menopausal status) and lifestyle factors (diet, physical activity, smoking status, obesity, alcohol and medication use) may influence postprandial hypertriglyceridaemia. This narrative review considers the studies published over the last decade that evaluated postprandial hypertriglyceridaemia. Additionally, the genetic determinants of postprandial plasma triglyceride levels, the types of meals for studying postprandial triglyceride response, and underlying conditions (e.g. familial dyslipidaemias, diabetes mellitus, metabolic syndrome, non-alcoholic fatty liver and chronic kidney disease) that are associated with postprandial hypertriglyceridaemia are reviewed; therapeutic aspects are also considered.
Keywords: familial dyslipidaemia